2022
DOI: 10.3389/fchem.2021.804981
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Flow Assay for the Detection of African Swine Fever Virus Antibodies Using Gold Nanoparticle-Labeled Acid-Treated p72

Abstract: African swine fever is a widespread and highly contagious disease in the porcine population, which is caused by African swine fever virus (ASFV). The PCR and ELISA detection methods are the main conventional diagnostic methods for ASFV antigen/antibody detection in the field. However, these methods have limitations of expensive equipment, trained technicians, and time-consuming results. Thus, a rapid, inexpensive, accurate and on-site detection method is urgently needed. Here we describe a double-antigen-sandw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…However, the p72 was shown to fail in forming trimers when expressed alone (Cobbold et al 2001 ). Interestingly, Zhu et al reported to express the 72 alone in yeast competent cells and obtain p72 trimers (Zhu et al 2022 ). In fact, the pB602L, an ASFV non-structural protein, has been described as a chaperone facilitating the correct folding of the p72 (Cobbold et al 2001 ; Epifano et al 2006 ; Meng et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the p72 was shown to fail in forming trimers when expressed alone (Cobbold et al 2001 ). Interestingly, Zhu et al reported to express the 72 alone in yeast competent cells and obtain p72 trimers (Zhu et al 2022 ). In fact, the pB602L, an ASFV non-structural protein, has been described as a chaperone facilitating the correct folding of the p72 (Cobbold et al 2001 ; Epifano et al 2006 ; Meng et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al have also utilized gold nanoparticle–labeled and acid-treated p72 to establish a lateral flow strip. The sensitivity of the strip is 1:10,000 for clinical positive sera (Zhu et al 2022 ). The sensitivity of our strip is 1:204,800, which is more sensitive than the commercial ELISA kit when testing positive standard serum.…”
Section: Discussionmentioning
confidence: 99%
“…Although ASF outbreaks had previously been limited in sub-Saharan Africa, an outbreak in Georgia in 2007 and its subsequent spread to neighboring countries in the south Caucasus, Europe, and the Russian Federation has highlighted the threat of ASF’s transboundary spread (Rowlands et al ., 2008; Sánchez-Vizcaíno et al ., 2015; Sauter-Louis et al ., 2021). Furthermore, ASF invaded China, the world’s largest pig producer in 2018, and then Southeast Asian countries, including Vietnam, continuing to have a devastating impact on the livestock industry and food security (Blome et al ., 2020; Le et al ., 2019; Wang et al ., 2020; WOAH, 2020; You et al ., 2021; Zhou et al ., 2018; Zhu et al ., 2022). As a result of the expansion of ASF, the pig industry has been suffering significant economic losses in ASF-endemic countries (Carriquiry et al ., 2020; Mason-D’Croz et al ., 2020; Nguyen-Thi et al ., 2021; WOAH, 2020; You et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Early pathogen detection is important when a disease lacks a vaccine as part of its prevention strategy. Thus, researchers have attempted to develop various serological diagnosis kits by using monoclonal antibodies (mAbs) against the ASFV immunogenic proteins such as [ 17 , 18 ] p. 72, [ 19 ] p. 62, [ 20 , 21 , 22 , 23 ] p. 54, [ 22 , 24 ] p. 30 , [ 25 ] p. 22 and others.…”
Section: Introductionmentioning
confidence: 99%